Illocutionary Act in Selected Maybelline Advertisements as an Alternative Source to Teaching Speaking - Setyasih Budi Wibawanti; Listyaning; Arso Setiaji (Melati Institute, 2023)
Language is one of the means of communication used to convey a particular purpose. Language, as a communication tool, can foster mutual understanding between speakers and speech partners, or between writers and readers. Language is not only use for daily communication it is also use in advertisements. In everyday communication sometimes what we say has a wide range of meanings hence the speech act plays a major role in revealing the true meaning of what uttarence say. Language skills can be one way to attract students. Illocutionary act in advertisement can be one of the learning media that attracts students such as commercial media advertisements especially use maybelline advertisement in this research can help to improve students speaking skill. This research used qualitative descriptive method. The data was collected using documentation, which then analyzed by using qualitative analysis. The four steps of qualitative analysis are data collection, data reduction, data display, and conclusion. The results of the research showed that illocutionary acts in selected Maybelline advertisements can (1) There are two types of illocutionary acts which found in 15 selected maybelline advertisements which are assertives or representative and directives (2) Illocutionary act already actualized as they are providing information towards the product. (3) the contribution of illocutionary act to the teaching and learning speaking can help the learners by providing direct examples from native speaker.